21.2: Invited Paper: The application of AMOLED in smart wearable technology. (28th November 2018) - Fan, Wenzhi; Cheng, Ji; Zhu, Xiujian; Du, Yang; Huang, Xiuqi
Abstract : Two approaches of fabrication of a 1.2 inch round AMOLED panel were discussed in this paper, in which one is glass+thin film encapsulation(TFE) and the other is polyimide(PI)+TFE. The innovative glass+TFE approach has the distinctive feature of ultra‐thinness compared to traditional glass+glass panel structure, and reduces yield loss in the PI and laser lift off(LLO) process compared to PI+TFE panel. The flexible PI+TFE approach can realize the bending of bottom border. Thus it fulfills true circular requirements for wearable displays.